On young modules of defect 2 blocks of symmetric group algebras - Chuang, J; Tan, K (Elsevier, 1999)
In this paper, we obtain the ordinary characters and module structures of the Young modules of defect 2 blocks of symmetric group algebras. We also study how these modules induce and restrict in a [2 : 1]-pair.